Redefining Surabaya's MSMEs Landscape: Unleashing Digital Virality for Sustainable Growth - Dyatmika, Sutama Wisnu; Suyanto, Bagong; Setijaningrum, Erna; Setioningtyas, Widhayani Puri (Economics, Business, Accounting & Society Review, 2024)
This study explores the effectiveness of digital marketing strategies, particularly viral content, in enhancing the visibility and sustainability of micro, small, and medium enterprises (MSMEs) in Surabaya City. This research utilizes a descriptive qualitative approach, combining literature review and stakeholder interviews as key data collection methods. Interviews were conducted with key MSME stakeholders in Surabaya to assess the implementation and impact of digital marketing strategies on business performance. The findings indicate that digital marketing, especially through viral content, is crucial in improving MSME visibility and long-term sustainability. Viral content effectively captures consumer attention, fosters online engagement, and strengthens brand recognition, ultimately contributing to business growth. This study offers valuable insights for MSME owners, policymakers, and support institutions seeking to optimize digital marketing strategies. Practical recommendations include enhancing content creation skills, fostering collaborations with local influencers, and leveraging social media platforms for broader market reach. These findings underscore the importance of strategic digital marketing in ensuring the competitiveness and resilience of MSMEs in an increasingly digitalized business environment.